The Extraordinary and the Ordinary: The Possibilities and Problems of Eberhard Jüngel’s Hermeneutics - Casewell, Deborah (Modern theology, 2026)
Eberhard Jüngel insists on the absolute transcendence of God and on human language as the vehicle for that transcendence. In doing so, he makes claims both about the power of language and the limits of humanity in relation to language. In exploring this tension, the essay will examine whether Jüngel successfully navigates the tension between transcendence and hermeneutics, looking at the ways forward he provides, as well as the questions raised by his solutions. The essay will note the influence of the New Hermeneutic and Heidegger’s late work on Jüngel’s understanding of metaphors and speech-events, and bring his insights into critical dialogue with the post-structuralism of Jacques Derrida and the stress on ordinary language in relation to the divine in Rowan Williams. I will argue that Jüngel’s stress on the passivity of the human in relation to the freeness of divine language can challenge Derrida’s argument that language is always deconstructive, and that Williams’s use of Wittgenstein can bring Jüngel’s thought back to the ordinary in productive ways. Both that freeness and that groundedness in language can then allow for more interaction between hermeneutics and transcendence to enable us to think with, but beyond, Jüngel’s hermeneutics.